A GAP ANALYSIS TO MEASURE SERVICE QUALITY OF UNIVERSITY LIBRARIES THROUGH USER PERSPECTIVES:A CASE STUDY AT THE UNIVERSITY OF COLOMBO - Somaratna, Sajeewanie D. (degree of MLIS, 2009)
In virtually any field of endeavour today access to information is a pre-requisite for success. Libraries form the repositories of information with user friendliness as their mission. This has led to the need for new ways to evaluate library performances. User satisfaction is an important measure of service quality in libraries. User perceptions about academic libraries seem to have been largely ignored by library management in developing countries. The assessment of service quality from the user perspective provides an important feedback for libraries to assess and improve their services. The aim of this research was to assess the overall service quality of the University of Colombo Library System through the users' perspectives to provide a better service to satisfy their expectations. A theoretical study of relevant literature and a user survey were used in this research. The theoretical study helped to identify relevant theories determining and defining service quality in Academic Libraries. A questionnaire was used in the user survey. A total of 614 users of the Colombo University Library system; Undergraduates, Postgraduates and Academic staff were taken as the sample. A modified version of a SERVQUAL model was used to ascertain the views of library users about service level. They were asked to assess the actual service delivered by the relevant library; to establish the importance of the service to them as users; and, to identify to what extent the service meets their expectations. The instrument items covered various aspects of service, such as the Library collection, Library Services, Physical Facilities and Service Delivery by staff. The study discovered that the service quality was represented by seven dimensions in the Colombo University Library system, relating to service delivery by staff, collection and access, E-resources and awareness, physical facilities, information control, library catalogue and security. The best predictor of the overall service quality was the dimension referred to as "Collection and Access" followed by "Information Control", "Service Delivery by Staff, "E-Resources and Awareness", "Security" and "Library Catalogue". This study has shown that all users desired expectations are not met. The largest service quality gap among all the attributes applied to the Colombo University Library System was "Access to electronic journals". Other gaps with higher gap scores were related to library catalogue, library collection and access, physical facilities and awareness. Further research is necessary to establish the findings of this survey. It is hoped that this would provide insights for further research in this field which in turn would eventually help decision makers to improve service quality in our academic libraries.